Ca/calmodulin-dependent phosphorylation of endocytic scaffold ITSN1 - Morderer, D.Ye.; Nikolaienko, O.V.; Skrypkina, I.Ya.; Rymarenko, O.V.; Kropyvko, S.V.; Tsyba, L.O.; Rynditch, A.V. (Вiopolymers and Cell, 2014)
ITSN1 is an endocytic scaffold protein with a prominent function in synaptic transmission. It is known that Ca signaling is crucial for the regulation of synaptic proteins functioning. Aim. Checking the possibility of Ca/calmodulin-dependent phosphorylation of ITSN1. Methods. Affinity chromatography, in vitro kinase reaction, Western blotting, gel staining with fluorescent stains. Results. We show that the fraction of calmodulin-binding proteins is able to phosphorylate the recombinant fragments encoding the coiled-coil region and the SH3 domain-containing region of ITSN1 in the presence of Ca ions and calmodulin. Conclusions. The coiled-coil region and the SH3 domain-containing region of ITSN1 undergo Ca/calmodulin-dependent phosphorylation in vitro, suggesting a possible regulation of ITSN1 by Ca signaling.